Needs assessment survey of healthcare providers’ perceptions and practices regarding delirium prevention at a university medical center - Alghamdi, Bushra; Koroukian, Siran M.; Kresevic, Denise; Drummond, Colin K. (Frontiers in Aging, 2022)
Background: Despite the high prevalence and serious implications of delirium, identification, tracking, and documentation of the condition remain a challenge for the health care team, impeding management of patients. This survey is the first phase of a qualitative study to build a conversational agent-based tool for screening and managing delirium-prone patients. Objectives: To assess healthcare providers’ perceptions of delirium management, focusing on patient assessment, therapeutic interventions, and subsequent communication and documentation. Design: An electronic web-based survey was distributed to healthcare providers identified as caring for inpatient acutely ill older adults admitted for medical and orthopedic surgery needs. Respondent contact information was removed to preserve anonymity. Setting: A 1,000 bed university-affiliated teaching hospital in an urban setting. Participants: 23 residents in family practice, 36 residents in internal medicine, and a total of 492 advanced care nurses, nurses, and clinical staff. Approach: The analysis of survey responses provided insight into providers’ current experiences with delirium assessment tools including computerized documentation, as well as their perceptions and attitudes toward delirium prevention. Key results: Most respondents (89%) thought delirium could be prevented, and 85% thought targeting delirium risk factors was helpful. Fifty one percent reported patients’ loneliness and need for companionship, and 65% believed delirium was linked to higher mortality. Only 14% of respondents thought existing Electronic Health Record (EHR) alerts to identify high-risk delirium patients were useful, and 38% thought current delirium assessment protocols were helpful. In addition, 33% of nurses never received formal delirium prevention training, and 48% indicated that they needed improved systems to assess and manage patients at risk for delirium. Conclusion: A majority of providers affirmed that current delirium protocols are helpful; however, existing screening instruments and methods for documentation are cumbersome, resulting in incomplete or limited documentation of episodes. These barriers lead to an understatement of evidence available for continuous improvement of the patient management process.